2014
DOI: 10.1186/1472-6882-14-23
|View full text |Cite
|
Sign up to set email alerts
|

Compound danshen tablet ameliorated aβ25-35-induced spatial memory impairment in mice via rescuing imbalance between cytokines and neurotrophins

Abstract: BackgroundCompound Danshen Tablet (CDT), a Traditional Chinese Medicine, has recently been reported to improve spatial cognition in a rat model of Alzheimer’s disease. However, in vivo neuroprotective mechanism of the CDT in models of spatial memory impairment is not yet evaluated. The present study is aimed to elucidate the cellular mechanism of CDT on Aβ25-35-induced cognitive impairment in mice.MethodsMice were randomly divided into 5 groups: the control group (sham operated), the Aβ25-35 treated group, the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
34
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 36 publications
(36 citation statements)
references
References 36 publications
2
34
0
Order By: Relevance
“…In the periphery, the production of TNF-α has also been confirmed as a key mediator of synaptic instability to contribute to sensory and cognitive deficits (Yang et al, 2013). In addition, many studies have shown that the inhibition of TNF-α is associated with an improvement of cognitive dysfunction Teng et al, 2014). Therefore, inflammatory mediators, such as TNF-α, may play an important role on the course of POCD development, and they may serve as new targets for the prevention of POCD after surgery.…”
Section: Discussionmentioning
confidence: 98%
“…In the periphery, the production of TNF-α has also been confirmed as a key mediator of synaptic instability to contribute to sensory and cognitive deficits (Yang et al, 2013). In addition, many studies have shown that the inhibition of TNF-α is associated with an improvement of cognitive dysfunction Teng et al, 2014). Therefore, inflammatory mediators, such as TNF-α, may play an important role on the course of POCD development, and they may serve as new targets for the prevention of POCD after surgery.…”
Section: Discussionmentioning
confidence: 98%
“…Amyloid β‐protein fragment 25–35 (Aβ 25–35 ) was purchased from Beijing Biosynthesis Biotechnology Co, LTD (Beijing, China). The Aβ 25–35 was dissolved in sterile saline at a concentration of 2 g/l and incubated at 37 °C for 7 days to allow for fibril formation as described previously …”
Section: Methodsmentioning
confidence: 99%
“…The MT‐200 Morris water maze (MWM) system (Chengdu TME Technology Co, Ltd, Chengdu, China) was used to assess the spatial learning and memory abilities in mice before and after the animal treatment as described previously . Twice training trails per day were conducted for four consecutive days, with an intertribal interval of 15 min.…”
Section: Methodsmentioning
confidence: 99%
“…47,49,50) The apparatus consisted of a circular pool (120 cm diameter ×60 cm height) with a black inner wall, which was subdivided into four equal quadrants and filled with water (25°C) to the depth of 30 cm. An escape platform (10 cm diameter) was placed in one of the quadrants (the target quadrant) and submerged approximately 2 cm below the surface of the water.…”
Section: Preparation Of Ostmentioning
confidence: 99%
“…investigate the effects of Ost on cognitive function of Tg mice, hippocampus-dependent learning and memory was analyzed using Morris water maze test after a six-week treatment with Ost. 49,50) Spatial learning was expressed as the latency of time spent on finding the escape platform in the water maze. 47) Significant differences among the three groups were observed (Figs.…”
Section: Ost Promoted Nscs Proliferation In a Notch Signalingdependenmentioning
confidence: 99%